Zur Kenntnis der subantarktischen und antarktischen Meeresalgen. II. Rhodophyceen. - Kylin, Harald, 1879-1949; Skottsberg, Carl, 1880-1963; Svenska sydpolar-expeditionen (1901-1903) (Stockholm : P.A. Norstedt, 1919)
Mode of access: Internet.